PEMBERIAN KOMPENSASI LANGSUNG DALAM MENINGKATKAN KINERJA KARYAWAN HOTEL HB BEACH BUTON UTARA - Dewi Dewi; Aminuddin Aminuddin; Nurjannah Nurjannah (Universitas Halu Oleo, 2020)
The purpose of this study was to determine the provision of direct compensation in improving the performance of employees of HB Beach Buton Utara Hotel.The research method used is